Hormone replacement therapy reduces lipid oxidation directly at the arterial wall: A possible link to estrogens' cardioprotective effect through atherosclerosis prevention - Escalante Gómez, Carlos (2018)
Background: The first step in atherosclerosis formation is the ingurgitation of an oxidized low‑density lipid (LDL) molecule by a macrophage which then turns into a foam cell within the vascular wall and initiates a cascade of inflammatory responses. Could it be that the potential cardioprotective effect observed in women receiving hormone replacement therapy (HRT) is modulated by estrogen’s capacity to decrease LDL oxidation in the vascular wall and thus decrease atherosclerotic foam cells? Materials and Methods: Thirty‑four adult female Wistar rats were divided into three groups. All were double oophorectomized. After recovery, Group 1 received Estradiol Valerate subcutaneous (SC) (2.5 mg/kg/week), Group 2 Estradiol Valerate SC (2.5 mg/kg/week) + Progesterone SC (10 mg/kg/48 h), and Group 3 Placebo SC. After 10 weeks, all rats were sacrificed and a vascular dissection performed. Malondialdehyde (MDA) was measured directly on the vascular extract to determine lipid oxidative levels and HRTs’ effect. Renal and hepatic tissue was also studied. Total antioxidant status (TAS) was measured to determine overall oxidative behavior. Results: Vascular MDA levels for Group 1 = 80.80 (±16.8) μmol/ml/g, Group 2 = 107.69 (±24.9) μmol/ml/g, and Group 3 = 140.96 (±32.4) μmol/ml/g. ANOVA (P < 0.05), with a post hoc Bonferroni corrective t‑test, showed that both Group 1 and 2 have statistically significant lower levels of MDA than Group 3. Renal tissue showed less oxidative damage in the HRT groups, while hepatic tissue showed an inverse behavior with less lipid oxidation in the placebo group. TAS decreased with oophorectomy in all groups but decreased less in both groups that received HRT compared to placebo (P < 0.05). Conclusion: HRT significantly reduces lipid oxidation directly in the arterial wall.